In the shadow of the church : the building of mosques in early medieval Syria - Guidetti, Mattia. (Arts and Archaeology of the Islamic World, 2016)
In his book In the Shadow of the Church: The Building of Mosques in Early Medieval Syria Mattia Guidetti examines the establishment of Muslim religious architecture within the Christian context in which it first appeared in the Syrian region, contributing to the debate on the transformation of late antique society to a Muslim one. He scrutinizes the slow process of conversion to Islam of the most important town centers by looking at religious places of both communities between the seventh and the eleventh century. The author assesses the relevancy of churches by analyzing the location of mosques and by researching phenomena of transfer of marble material from churches to mosques.